Factor Influence Paying Zakat Using Digital Payment - Waluyo (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
This study aims to see what factors encourage people to pay zakat through a digital (online) platform using Islamic mobile banking. This study uses the population of Sragen people who have made digital payment transactions in paying zakat using Islamic mobile banking. Samples were obtained 100 respondents with random sampling technique. The theoretical approach uses the technology acceptance model (TAM) which is expanded with knowledge and religiosity variables. While the data analysis used multiple linear regression analysis. The results show that perceived usefulness, knowledge and religiosity variables influence people's decisions to pay zakat digitally (online) using Islamic mobile banking. While the perceived ease of use has no significant effect. This is due to infrastructure factors that have not been able to reach the area optimally, so even though the application used is easy but not supported by adequate internet facilities, the accessibility is limited.